“The natural highs, the opening gate, the stile to another somewhere…: A single case study of one client’s experience of walk and talk therapy - Revell S; McLeod J (John Wiley & Sons Ltd, 2026)
Background: Interest in and the provision of therapeutic methods that integrate the beneficial effects of nature to support overall mental health and well-being is growing. Walk and talk therapy is a therapeutic activity that combines walking in an outdoor setting with traditional counselling and psychotherapy practice. Distinctive change processes associated with walk and talk therapy are not yet fully understood. This study reports on the findings from a narrative case study of one client's experience. Method: This study utilised a walk and talk interview to generate a nuanced and place-specific understanding of the process of change within one client's experience of walk and talk therapy. Findings are creatively presented with the use of stanza and reflective researcher accounts of the process. Findings: The outdoor setting, physicality and metaphor were key elements of a therapy experience that was highly meaningful and helpful for this client. Conclusion: This study provides contextual understanding of one person's experience of walk and talk through the novel approach of a walking interview. Findings highlight the important relationship between therapy and place, which incorporate client preferences. Implications for further research are discussed along with suggestions for therapists, who might like to integrate this therapeutic activity within their practice.